A study on the conversion relationship of noise perceived annoyance and psychoacoustic annoyance—a case of substation noise. Issue 2 (June 2022) - Guoqing, Di; Cong, Chen; Yao, Yao; Li, Dong; Jian, Wu
The level of annoyance is an important basis to determine the acceptable degree of noise and develop noise standards. Psychoacoustic annoyance ( PA ) calculated by Zwicker's model and perceived annoyance (such as mean annoyance, MA and the percentage of highly annoyed population, % HA ) obtained through individual self-reports are widely used. PA and MA (or %HA ) cannot be directly compared because the ranges of their values are different. Thus, the conversion relationship of PA and MA (or %HA ) needs to be developed. As a case study, the model between PA and MA (or %HA ) of substations noise was established and the rationality of model was verified. Results showed that the maximum value of the difference of MA (or % HA ) between the calculation result of model and experimental result was less than 0.89 (or 15%). In this way, the perceived annoyance of substation noise samples can be determined by calculation without experiments.